ANALYSIS OF SPORTS ACHIEVEMENTS OF ATHLETIC, BADMINTON AND BASKETBALL IN THE SCHOOLS OF MORADABAD COMMISSIONARY (Conferencea, 2024)
The study aimed to analyze the Sports Achievements of Athletic, Badminton and Basketball in the schools of Moradabad Commissionary. In this regard, the researcher surveyed 30 senior secondary level schools of the U.P. board, under the radius of Moradabad Commissionary. The random sampling method was used to select the schools for data collection. Copies of the survey scale with covering letters were given to the school principal/physical education teacher, requesting that they give correct and accurate answers and return them as soon as possible. As per the objectives of the study, the Percentage method was used for assessing and analyzing the data.